Hereditary Neuropathy with Analysis of Electrophysiological Findings: A Case Report (Journal of National Institute of Neurosciences Bangladesh, 2017)
The hereditary motor and sensory neuropathies (HMSN) represent a genetically heterogeneous collection of disorders in which patients develop a progressive muscular atrophy and sensory neuropathy of the distal extremities. There are abnormalities of axons or Schwann cells and their myelin sheaths resulting in peripheral nerve dysfunction. These disorders are also known as Charcot-Marie-Tooth (CMT) disease, which is divided into seven distinct subtypes based on inheritance pattern (dominant, recessive, or X-linked) and whether the primary pathology is located in the myelin or axon. Each of these CMT types are further divided based on their specific molecular and genetic findings. Here we report a case which was diagnosed on the basis of clinical history and neurophysiological testing. Although genetic analysis is the gold standard for diagnosis we could not do it due to lack of availability of genetic testing in our country at this moment.Journal of National Institute of Neurosciences Bangladesh, 2016;2(1): 43-45